Semiotic analysis of sexual harassment representation in the film “Penyalin Cahaya” - Kirana Pinkan Permata Rudy; Christina Nur Wijayanti (Jurnal Mantik, 2023)
he purpose of this study is to describe what representations of sexual harassment are contained in the film "Penyalin Cahaya". The research method used is descriptive qualitative with Roland Barthes’ semiotic analysis theory which focuses on the meaning of denotation, connotation, and myth. The results of the study found there are 12 (twelve) scenes that contain representations of sexual harassment in the film, such as stealing personal photos, drugging the victim before committing sexual harassment, nudity, photographing the victim's body and using its visuals for certain purposes without the consent of the victim. The results of the analysis of the 12 (twelve) scenes also describe representations of social issues related to sexual harassment, namely the culture of victim-blaming, sexual harassment that is not based on the victim’s gender, patriarchal culture in regulating the victim’s way to dress and behave, abuse of power, and the victim’s fear being stigmatized by society